Representações sociais dos direitos humanos construídas por mães de estudantes de diferen-tes contextos socioeducativos - Queiroz, Pablo Vicente Mendes de Oliveira (2011)
The aim of this study was to verify how mothers whose children have studied in different social and educational contexts represent the Human Rights HR of different genera-tions. The analysis of Social Representations SR focused on several aspects of HR: objectivations, which HR are known, knowledge source about HR and their definition. For this research, it was adopted the Norberto Bobbio and Celso Lafer s perspective about the generations of HR. Moreover, it was studied the SR of HR based on Serge Moscovici and Willem Doise s theories. Regarding Willem Doise s theory it was considered three as-pects: the representational field, organizing principles and social anchors. Besides the theo-retical approaches mentioned above, several empirical studies supported this research. It was supposed this study may contribute to a new field of research that links the SR theory to maternal socialization theory. This study was carried on with a hundred and twenty mothers equally distributed into two groups: 1- mothers whose children have studied in public schools and 2- mothers whose children have studied in private schools. Mothers were asked about: 1- social and demographic issues, 2- free word association, 3- which HR are known, 4- the definition of HR, 5- which rights of children and adolescents are known and 6- questions about rights from different generations. Data were analyzed by the soft-ware Alceste. Among the results, it is emphasized that in all questions some participants showed a negative and restricted view of HR related to mothers of low socioeconomic level and low level of education. Whereas other participants showed a positive and broad view of HR related to mothers of medium socioeconomic level with graduation degree. It is supposed these results can be explained by the fact that mothers from medium socioeco-nomic level have broader access to HR. It is important to emphasize that some participants considered that the government is responsible for the implementation of HR. It was related to mothers of medium socioeconomic level and with graduation degree. It was supposed that this view required a good level of information in general .